Kamus Dewan Perdana: A Glimpse at Etymological Information - Collins, James Thomas (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
In 2020, Kamus Dewan Perdana (KDP) made its appearance on the stage of history as the best Malay dictionary since the publication of Wilkinson’s dictionary in 1932—almost one hundred years ago. Among the aspects of KDP that stand out as praiseworthy is the effort to present etymological information for some of the entries. In this essay, a few of the 7000 etymologies found in KDP were selected as data to be compared with the format and content of etymologies in other general dictionaries. The etymologies selected here include both inherited words and loanwords. Furthermore, the problems of confusing etymologies as well as gaps in etymological information in KDP are also reviewed. By surveying selected examples in this way, it becomes obvious that any revisions to KDP’s etymological information must be based on a standard operating procedure (SOP) that should be discussed and decided together. Full text : PDF